Pengaruh Kepemimpinan Situasional Kepsek dan Sarpras terhadap Kinerja pada SLTA Yadika se-Jabodetabek - Irawan, Pristanto Ria; Junengsih, Junengsih; Nuridah, Siti (https://jurnal.binamandiri.ac.id/, 2022)
The purpose of this study was to determine the extent of the influence of the principal's situational leadership and facilities on the performance of employees at Yadika Senior High Schools throughout Jabodetabek. This study uses quantitative research methods with data collection techniques through the distribution of questionnaires and literature. In this study, the sample used was 96 educators and education staff at Yadika Senior High Schools throughout Jabodetabek. The data analysis technique used is multiple linear regression analysis using the SPSS application. The results showed that; The situational leadership variable of the principal partially has a significant effect on the performance of school employees, the infrastructure variable has a significant effect on the performance of school employees, while the situational leadership variable of the principal and infrastructure simultaneously or simultaneously has a significant effect on employee performance with a percentage of 52,9 %, while the remaining 47,1% is influenced by other factors not examined in this study.